Pengaruh Pengetahuan dan Persepsi Masyarakat Terhadap Minat Menggunakan Pembiayaan Murabahah di Baitul Maal Wat-Tamwil Al-Ishlah Kota Jambi - Via Ullya Syafitri; Agustina Mutia; Mohammad Orinaldi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Economic life cannot be separated from the important role of the financial services sector in general and banking in particular. It is through this media that the aim is to realize a healty economy by empowering existing funds or investment potential in the community which can be channeled into various productive activities so that healthy economic growth can be achieved and avoid usury. There are several financing products such as mudharabah, ar-rahn, and qardhul hasan. Baitul Maal Wat-Tamwil to provide financing to small businesses cannot possibly be replaced by sharia banks, because it is impossible for sharia banks to operate in small scale financing, while the community needs small capital. The purpose of this study was to determine the effect of knowledge the intention to use murabahah financing in the Baitul Maal Wa-Tamwil Al-Ishlah, Jambi City, to determine the effect of public perceptions on yhe interest in using murabahah financing in the Baitul Maal Wat-Tamwil Al-Ishlah, Jambi City, and to determine the influence of public knowledge and perceptions of interest in using murabahah financing in Baitul Maal Wat-Tamwil, Jambi City. This research is a quantitative research, collecting data using questionnaires and questionnaires. The sampel for this research was the local community in RT 19, Simpang IV Sipin Subdistrict, Telanaipura District, Jambi City, totaling 86 peole. The reseacrh results show that the variables of knowledge and public perception influence interest in using murabahah financing. The results of calculating the coefficient of determination show that the variables of knowledge and public perception are 76,9% and 23,1% influenced by other variables outside this reseach.